2013
DOI: 10.1167/iovs.13-13121
|View full text |Cite
|
Sign up to set email alerts
|

Nonselective Assembly of Fibrillin 1 and Fibrillin 2 in the Rodent Ocular Zonule and in Cultured Cells: Implications for Marfan Syndrome

Abstract: These data suggest that fibrillin 1 assembly and fibrillin 2 assembly share similar mechanisms. Microfibril composition depends substantially on the local levels of fibrillin isoforms and is not highly selective in regard to the isoform. This raises the intriguing possibility that the zonule could be strengthened in MFS by inducing fibrillin 2 expression in ciliary epithelium. The presence of fibrillin 2 in the murine zonule and an intact zonule in Fbn1-knockout mice may limit the utility of rodent models for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 44 publications
5
53
0
Order By: Relevance
“…In retinal pigment epithelial cells, microfibril assembly was independent of fibronectin, but required syndecan-4, consistent with an observed agonistic effect of heparin–sulfate proteoglycans on microfibril assembly [7,38,39]. However, microfibril assembly in human non-pigmented ciliary epithelial cells was fibronectin-dependent, suggesting that even epithelial cells may have different requirements for fibrillin assembly, presumably owing to diversity of their secretomes [34]. …”
Section: Fibrillin Assembly and Microfibril Functions: Insights From supporting
confidence: 53%
See 3 more Smart Citations
“…In retinal pigment epithelial cells, microfibril assembly was independent of fibronectin, but required syndecan-4, consistent with an observed agonistic effect of heparin–sulfate proteoglycans on microfibril assembly [7,38,39]. However, microfibril assembly in human non-pigmented ciliary epithelial cells was fibronectin-dependent, suggesting that even epithelial cells may have different requirements for fibrillin assembly, presumably owing to diversity of their secretomes [34]. …”
Section: Fibrillin Assembly and Microfibril Functions: Insights From supporting
confidence: 53%
“…Fibrillin isoforms can form microfibrils by homotypic or heterotypic head-to-tail and lateral self-assembly [30–33]. During this process, microfibrils are thought to incorporate fibrillin isoforms indiscriminately depending on their availability at the time of assembly [30,31,34]. FBN2 and FBN3 mRNA expression is prevalent during embryogenesis and FBN1 mRNA is prevalent after birth; therefore, it is generally accepted that the preponderance of FBN1 in adult microfibrils reflects the relatively abundant postnatal expression of this isoform [3537].…”
Section: Fibrillin Assembly and Microfibril Functions: Insights From mentioning
confidence: 99%
See 2 more Smart Citations
“…FBN1 binds to each other and forms microfibrils with other proteins, which enables the skin, ligaments, and blood vessels to stretch, and supports more rigid tissues such as nerve, muscle, and lenses of the eyes [12]. Mutations in FBN1 gene can result in Marfan syndrome [13, 14], a disorder that affects the connective tissue supporting the body's joints and organs, and Weill-Marchesani syndrome that causes the eye, heart, and skeletal abnormalities [15]. Growing studies have revealed that FBN1 also functions to regulate organ development and homeostasis [16], integrin α5 assembly [17], and gremlin-1 localization in tumor microenvironment [18].…”
Section: Introductionmentioning
confidence: 99%